2011
DOI: 10.1063/1.3589702
|View full text |Cite
|
Sign up to set email alerts
|

Micro Machining of Different Steels with Closed Electrolytic Free Jet

Abstract: Electrochemical Machining (ECM) with closed electrolytic free jet (Jet-ECM) is an innovative procedure in micro manufacturing technology which is based on anodic dissolution of metallic work pieces. Main advantage of Jet-ECM in comparison to other ECM processes is the restriction of the electric current to a limited area by the jet. Micro structured surfaces and complex three-dimensional micro geometries can be machined by help of different nozzle movements. In this study the Jet Electrochemical Machining is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…By a simplification assuming that z = const. , V sp represents a material constant, which is calculated according to Equation (4) [21]. Vsp=Mρ·z·normalF…”
Section: Methodsmentioning
confidence: 99%
“…By a simplification assuming that z = const. , V sp represents a material constant, which is calculated according to Equation (4) [21]. Vsp=Mρ·z·normalF…”
Section: Methodsmentioning
confidence: 99%
“…An important parameter which affects the cavity widths and depths is nozzle speed. Figure 9(c) shows the variation of cavity depths with nozzle speed [66]. It can be observed that the cavity depths are higher at lower nozzle speeds due to increase in specific dissolution volume.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…EJP in subtractive mode has been successfully applied in creating meso-and micro-scale surface structures across a wide range of materials [15][16][17][18][19][20][21] and applications [22][23][24][25][26]. Prior research work has been carried out to enhance EJP through modification to the nozzle tip [13], enabling modulation of the machined profile, which is distinct from that resulting due to the Gaussian energy distribution ( Fig.…”
Section: Introductionmentioning
confidence: 99%